Geochemical Insights into Rare Earth Elements Distribution patterns in Granites of Nasarawa State, North-Central Nigeria - Salihu , Mohammed; Joseph, Emmanuel; Baba-Kutigi, Adamu N. (Journal of Physical Sciences, 2026)
Purpose: To investigate the distribution of rare earth elements (REEs) in granites from selected locations within Nasarawa State, North-Central Nigeria, in order to evaluate their geochemical characteristics and assess their mineralization potential. Methodology: Fourteen (14) granite samples were systematically collected and analyzed using Instrumental Neutron Activation Analysis (INAA) at the Centre for Energy Research and Training, Ahmadu Bello University, Zaria, Nigeria. Trace element concentrations and REE patterns were examined, and geochemical discrimination diagrams were employed to determine tectonic settings and source characteristics. Findings: The trace element data show elevated concentrations of U (6.79 ppm), Co (64.81 ppm), Rb (266.89 ppm), Sb (2.04 ppm), Cs (43.83 ppm), and Ta (219.90 ppm) relative to Upper Continental Crust values, indicating moderate to extreme enrichment. REE patterns are dominated by light rare earth elements (LREE; average 58.44 ppm) over heavy rare earth elements (HREE; average 18.22 ppm). Geochemical discrimination diagrams indicate that the granites were emplaced in multiple tectonic settings, including syn-collisional, volcanic arc, and within-plate environments, and were primarily derived from the upper continental crust. Comparative analysis shows general depletion of most REEs, except for dysprosium (Dy), which exhibits elevated concentrations, suggesting potential Dy mineralization. Unique Contribution to Theory, Practice and Policy: This study provides baseline geochemical data for REE distribution in granites of Nasarawa State and contributes to the understanding of crustal evolution and tectonic settings in the region. It highlights the potential for dysprosium mineralization, offering practical insights for targeted REE exploration and resource development. The findings can inform mineral exploration strategies, guide investment decisions, and support policy formulation aimed at sustainable exploitation of REE resources in Nigeria.